2001
DOI: 10.1093/jn/131.5.1485
|View full text |Cite
|
Sign up to set email alerts
|

Beans, as a Source of Dietary Fiber, Increase Cholecystokinin and Apolipoprotein B48 Response to Test Meals in Men

Abstract: Dry beans lower plasma cholesterol, an effect that has been associated with both the fiber and the protein content of beans. The objective of this study was to determine the acute hormone and lipid responses to a test meal that contained dry beans as a source of dietary fiber. A crossover design was employed in which men consumed the test meal and a control meal in random order. Both meals contained egg, bread, jelly, orange juice, milk and margarine. The high fiber meal contained white beans, whereas the low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 39 publications
1
41
0
1
Order By: Relevance
“…The fact that reduced post-prandial ghrelin was observed lends support for a strong role for the properties of solid foods. CCK responds to dietary protein [13] and fiber [24]. Specifically, Bourdon et al found that CCK was twice as high following the consumption of a high fiber meal compared to a low-fiber meal [24].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that reduced post-prandial ghrelin was observed lends support for a strong role for the properties of solid foods. CCK responds to dietary protein [13] and fiber [24]. Specifically, Bourdon et al found that CCK was twice as high following the consumption of a high fiber meal compared to a low-fiber meal [24].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated the highly satiating effect of legumes (Anderson et al, 1999;Bourdon et al, 2001), therefore, further studies specifically investigating the satiating effect of chickpea-containing products are warranted. Such studies should employ higher incorporation rates of chickpea ingredients, larger numbers of subjects and more sensitive food intake measures (such as closely monitored food boxes supplied by researchers).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fiber is described as the material that has the ability to be resistant to digestion and absorption in the human small intestine along with absolute or segmental fermentation (Camire et al, 2001;Tabung et al, 2012). It has been illustrated that numerous researchers have offered more detailed information and showed that dietary fiber as an important functional food is capable of absorbing some of the human bodies' harmful substances, strengthening the immune systems and helping prevent some diseases such as high blood pressure and heart disease & Clydesdale (Behall et al, 2006;Bourdon et al, 2001;Pandolf & Clydesdale, 1992). Simultaneously, it has been confirmed adding a certain amount of dietary fiber into daily food products is secure and beneficial in recent years.…”
Section: Introductionmentioning
confidence: 99%